Stress and its associated psychosocial factors among Malaysian gifted students - Ali, Adli; Z., M. Amizul; H. A. R., Hanissa; A. S., Amira; L., Kexin; A., Anizah; Ishak, Shareena; J., Rohana (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
Introduction-The gifted students in Malaysia are housed together in a residential school which provides a competitive, yet stressful environment. The high expectations for academic achievement coupled with perpetual public expectations to be the “future elites” in the society could have made them vulnerable to stress and other psychological disturbances. Objectives-The aims of this study were to assess the prevalence and level of stress among Malaysian gifted students, to determine its correlation with depression and anxiety, and to evaluate its association with academic performance and other socio-demographic factors. Methods-A cross-sectional study was conducted on 227 Malaysian gifted students aged between 16-18 years old, based at PERMATApintar™/ASASIpintar, National University of Malaysia (UKM). Respondents were assessed through self-administered Depression Anxiety Stress Scale-21(DASS-21) questionnaires. Data on socio- demographics, family characteristics and academic performance were also obtained and analysed. Results-Stress was detected in 117 (52.9%) respondents and the mean stress score was 15.6±7.5. Out of those with stress, 43% experienced moderate level of stress, followed by mild level of stress (40%) whilst the remainder 17% experienced severe or extremely severe level of stress. Male students had significantly higher mean stress scores compared to female students (15.7±8.3 vs. 15.5±6.7, p<0.05). Stress was noted to be positively and significantly correlated with depression (r=0.682, p<0.01) and anxiety (r=0.704, p<0.01). There was no significant association between mean stress scores and academic performance, race, parental marital status and total family income. Conclusion-Stress is highly prevalent and is positively correlated with depression and anxiety among these gifted students. The sources of stress need to be explored in a positive perspective. Early screening for detection of pathological stress is highly recommended and promptly managed by a multidisciplinary team.